Povezivanje prakse i visokog obrazovanja na Univerzitetu u Sarajevu: pravni okvir, izazovi i perspektive / Linking Practice and Higher Education at the University of Sarajevo: Legal Framework, Challenges and Perspectives (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The focus of this paper is the representation of professional practice at the University of Sarajevo, its legal framework, challenges, and perspectives. Our higher education system has a well-established theoretical framework but no satisfactory professional practice that accompanies it. Although professional practice is envisaged as the application of acquired theoretical knowledge in a broader social context, for the general benefit of society, it is not sufficiently recognized or appropriately valued. Therefore, this paper examines the possibilities of increasing the scope and the level of practice, applying the acquired knowledge with the support of recruited experts and lecturers from the practice, and raising the criteria for evaluating students' practical knowledge. Considering the specificity of scientific research in legal science, the methods of scientific cognition are also specific. Normative and comparative methods will be applied in this paper. The intention of the authors is to provide a detailed analysis of the cooperation agreement between the University of Sarajevo and competent institutions in the field of employment and economy in order to create preconditions for the implementation of practical training in legal entities in the public and private sector and to identify possible solutions in adapting the learning outcomes to market needs.
Keywords: higher education; legal framework; learning outcomes; experts in practice; professional practice